Linguistic Interference and Integration in the Television Program 'Enah Bikin Enak' Broadcasted on Trans 7 - Risma Hikmah Rahmadini; Muhamad Hasbi Assidiq; Budi Rahayu Setiawan; Derin Fauzan Adzimarismahikmah@upi.edu; Annisa Azizah; Temmy Widyastuti; Nunuy Nurjanah (Bahasa Indonesia Prima, 2025)
The dynamics of language use in multilingual Indonesian society give rise to language interference and integration. This study aims to identify the forms of language interference and integration in the television show 'Enah Bikin Enak' aired on Trans 7. This research uses a descriptive qualitative method with data collection techniques through literature study and documentation of several show episodes. The data were analyzed to find forms of interference and language integration between Sundanese and Indonesian. The results showed several forms of interference in phonology, morphology, and syntax. In addition, regional vocabulary and expressions are integrated into the Indonesian language used in the show. These findings reflect the dynamics of language use in mass media, which cannot be separated from the influence of social and cultural developments.